Age dynamics of strongylatoses of sheep’s digestive system in the territory of Poltava region - Мельничук, В. В.; Степанюк, В. К. (Scientific Progress & Innovations, 2016)
In the work we present data about the level of infestation of different age groups of sheep by strongylates of gastrointestinal tract in conditions of farms in Zin’kiv, Shyshaky, Kobeliaky district of Poltava region. As a result of scatoscopic researches we established wide spread of strongylatosis pathogens in sheep (EI – 54,60 %) and proved their associative course with monieziosis, eimeriosis, trichuriasis, strongyloidosis. The highest extensiveness and intensity of strongylatosic infestation (EI – 69,66 %, ІІ – 295,51 ± 26,02 eggs in 1 g of feces) was recorded in young sheep aged from one to two years.